Ranirestat Improved Nerve Conduction Velocities, Sensory Perception, and Intraepidermal Nerve Fiber Density in Rats with Overt Diabetic Polyneuropathy. (18th November 2019) - Asano, Saeko; Himeno, Tatsuhito; Hayami, Tomohide; Motegi, Mikio; Inoue, Rieko; Nakai-Shimoda, Hiromi; Miura-Yura, Emiri; Morishita, Yoshiaki; Kondo, Masaki; Tsunekawa, Shin; Kato, Yoshiro; Kato, Koichi; et al.
Abstract : Distal sensory-motor polyneuropathy is one of the most frequent diabetic complications. However, few therapies address the etiology of neurodegeneration in the peripheral nervous systems of diabetic patients. Several metabolic mechanisms have been proposed as etiologies of this polyneuropathy. In this study, we revisited one of those mechanisms, the polyol pathway, and investigated the curative effects of a novel strong aldose reductase inhibitor, ranirestat, in streptozotocin-induced diabetic rats with preexisting polyneuropathy. Twelve weeks after the onset of diabetes, rats which had an established polyneuropathy were treated once daily with a placebo, ranirestat, or epalrestat, over 6 weeks. Before and after the treatment, nerve conduction velocities and thermal perception threshold of hindlimbs were examined. After the treatment, intraepidermal fiber density was evaluated. As an ex vivo assay, murine dorsal root ganglion cells were dispersed and cultured with or without 1  μ mol/l ranirestat for 48 hours. After the culture, neurite outgrowth was quantified using immunological staining. Sensory nerve conduction velocity increased in diabetic rats treated with ranirestat (43.3 ± 3.6  m/s) compared with rats treated with placebo (39.8 ± 2.3 ). Motor nerve conduction velocity also increased in the ranirestat group (45.6 ± 3.9 ) compared with the placebo group (38.9 ± 3.5 ). The foot withdrawal latency to noxious heating was improved in the ranirestat group (17.7 ± 0.6  seconds) compared with the placebo group (20.6 ± 0.6 ). The decrease in the intraepidermal fiber density was significant in the diabetic placebo group (21.6 ± 1.7 /mm) but not significant in the diabetic ranirestat group (26.2 ± 1.2 ) compared with the nondiabetic placebo group (30.3 ± 1.5 ). Neurite outgrowth was promoted in the neurons supplemented with ranirestat (control 1446 ± 147   μ m/neuron, ranirestat 2175 ± 149 ). Ranirestat improved the peripheral nervous dysfunctions in rats with advanced diabetic polyneuropathy. Ranirestat could have potential for regeneration in the peripheral nervous system of diabetic rats.